Drivers of change to e-grocery: an investigation of consumers’ channel choice - Hassan Alkhiyami (19198051) (2025)
Throughout and beyond the last COVID-19 pandemic, there has been widespread adoption and rapid development of online grocery (e-grocery) shopping. Groceries are one of the big retail industries wherein the adoption of multi-channel or omnichannel strategies is common. Pure online players are also prevalent. The situation varies across countries. We found no previous research investigating consumer behavior towards grocery channels in Qatar. This is hence the first paper targeting Qatar as a case study to explore consumers' decision to adopt the e-grocery and factors that impact their behavior. We adopted stated preference (SP) methods and developed an experimental design with two alternatives (Online shopping and Physical stores) and six attributes. Additional socio-demographic variables were incorporated into the pre-questionnaire to facilitate consumer segmentation. A Multinomial Logit model was developed to analyze the SP survey data. The same model was applied to sub-samples to identify consumer segments exhibiting different behaviors toward grocery channel choice. Results show that price, delivery cost, and lead time are major factors impacting consumer choice. Moreover, consumers were segmented into four categories, each valuing variable differently. An industrial validation of these findings provided actionable insights and strategic recommendations for policymakers and grocery retailers, addressing key aspects of consumer behavior and channel deployment. Other Information Published in: Electronic Commerce Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10660-025-10001-7